Can Motivation Shape Service Talk? ARCS Model to Enhance Hospitality Students’ Speaking Performance - Muhammad Bambang Purwanto; Achmad Leofaragusta Kurniawan Komerendo; Herman Herman (Foreign Language Instruction Probe, 2026)
This study aims to investigate the application of the ARCS model in improving students' speaking performance in the D3 Language and Tourism Program at the Sriwijaya State Polytechnic, Palembang. The research uses the Classroom Action Research design, which is carried out in two cycles, each including the planning, action, observation, and reflection stages. The research participants consisted of 30 second-semester students in the English for Hospitality course. The research instruments include role-play-based speaking tests, ARCS observation checklists, field notes, interviews, and speaking rubrics. The results showed that students' speaking skills before the implementation of ARCS were still in the low category, with limitations in fluency, vocabulary, and interactional competence. After implementing the ARCS model through authentic hospitality activities, there was a significant increase in student participation, confidence, and interaction quality. The average speaking score increased gradually from the initial condition to Cycle 1 and reached an optimal increase in Cycle 2, followed by a shift toward more spontaneous and communicative behavior. The study's findings also show that the components of Attention, Relevance, Confidence, and Satisfaction contribute to increased motivation to learn among students. Overall, the application of the ARCS model is effective in improving hospitality students' speaking skills and fostering more interactive, context-based learning. This study recommends the use of motivation-based learning design in vocational education to improve students' communication readiness in the world of work